Inwentarz przedmiotów pozostawionych przez Antoniego Malczewskiego - Dambek-Giallelis, Zofia (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
In the article, the inventory of Antoni Malczewski’s belongings, the author of the romantic poem Maria, is published. The document was found in the archive of Jan Feliks Wilski, a nineteenth-century Varsovian notary. The only time the document was sourced was in the biography of Malczewski by Władysław Kazimierz Wójcicki in 1854 (1855). Besides presenting the document, the author collates the rediscovered list with a reading by the nineteenth-century biographer.